Tetrabenazine as antichorea therapy in Huntington disease: a randomized controlled trial (Neurology, 2006)
Tetrabenazine (TBZ) selectively depletes central monoamines by reversibly binding to the type 2 vesicular monoamine transporter. Open-label reports indicate TBZ is effective in treating chorea. To examine the safety, efficacy, and dose tolerability of TBZ for treating chorea in Huntington disease (HD). The authors randomized 84 ambulatory patients with HD to receive TBZ (n = 54) or placebo (n = 30) for 12 weeks. TBZ was increased over 7 weeks up to a maximum of 100 mg/day or until the desired antichoreic effect occurred or intolerable adverse effects supervened. The primary outcome was the change from baseline in the chorea score of the Unified Huntington's Disease Rating Scale (UHDRS) RESULTS: TBZ treatment resulted in a reduction of 5.0 units in chorea severity compared with a reduction of 1.5 units on placebo treatment (adjusted mean effect size = -3.5 +/- 0.8 UHDRS units [mean +/- SE]; 95% CI: -5.2, -1.9; p < 0.0001). There was also a significant benefit on ratings of clinical global improvement. There were five study withdrawals in the TBZ group and five serious adverse events (SAEs) in four subjects (drowning suicide, complicated fall, restlessness/suicidal ideation, and breast cancer) compared with one withdrawal and no SAEs in the placebo group. Tetrabenazine (TBZ), at adjusted dosages of up to 100 mg/day, effectively lessens chorea in ambulatory patients with Huntington disease. TBZ should be dosed individually based on ongoing assessment of possible adverse side effects.